THE INFLUENCE OF SALES AND OPERATIONAL COSTS ON NET INCOME (CASE STUDY ON TEXTILE AND GARMENT SUB-SECTOR MANUFACTURING COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE 2015 - 2022) - Nastiti Rizky Shiyammurti; Sindy Supartini (Jurnal Scientia, 2023)
This study aims to determine the effect partially and simultaneously of variable sales and operating costs on net income. The problem that occurs in this research is the fluctuating net income, this research was conducted at textile and garment sub sector manufacturing companies that are listed on the Indonesia Stock Exchange from 2015-2022. The method of analysis in this study uses multiple linear regression analysis with the help of SPSS 26 software. The results of regression analysis test show that sales partially have a positive and significant effect on net income, operating costs partially have a negative and significant effect on net income, while simultaneously sales and operating costs have a significant effect on net income. To test the coefficient of determination or R2, the results are 0.623 or 62.3%, both of these variables affect net income. 37.7% for the rest is influenced by other variables not examined in this study.